Adapting the comprehensive assessment of acceptance and commitment therapy processes (CompACT) questionnaire for contextual relevance in Uganda: A comprehensive approach - Joseph Mugarura; Khamisi Musanje; Michael E. Levine; Ronald Asiimwe; Morris Ndeezi; Simon Kizito; Ross G. White; Rosco Kasujja (Cambridge Prisms: Global Mental Health)
The global utility of acceptance and commitment therapy highlights the need for adapting measures that can effectively capture the richness of psychological flexibility. One such instrument is the Comprehensive Assessment of Acceptance and Commitment Therapy Processes (CompACT). We translated the CompACT into Luganda and adapted it for use in Uganda. The original CompACT was translated into the Luganda language and reviewed through a series of evaluations. Nine mental health professionals participated in one-on-one interviews, while a focus group of eight culturally competent laypersons provided further insights. Their feedback resulted in revisions to enhance the instrument’s clarity, relevance, acceptability and completeness. The revised version was then cognitively tested with n = 25 trainees at Makerere University. Input from these various groups was synthesized and triangulated to develop the final version. A total of 23 items were adapted to improve the comprehensibility and completeness of the scale. Overall, respondents deemed the tool clear and acceptable. This study highlights the importance of a rigorous adaptation process, including translation, expert review, cognitive testing and feedback triangulation, to ensure psychological measures remain valid and relevant across cultures. Such an approach ensures accuracy in diverse contexts and provides a model for adapting psychological instruments for non-Western populations.